Acute Administration of Methionine Affects Performance of Swiss Mice in Learning and Memory Paradigms (Nigerian Journal of Physiological Sciences, 2021)
Summary: Methionine, an essential amino acid, plays an essential role in the central nervous system CNS development. It serves as a crucial intermediate in the methylation, trans-sulfuration and amino- phosphorylation pathways, necessary for the synthesis of nucleic acids, phospholipids, hormones, neurotransmitters, antioxidants, polyamines, catecholamines and other biogenic amines. The effect of methionine on learning and memory in mice was investigated using Morris water maze (MWM), Elevated plus maze(EPM) and Y maze (YM). Animals were administered with distilled water (control), methionine (1,700mg/kg); folate (3mg/kg) or methionine (1700mg/kg) plus folate (3mg/kg) for 14 days. Escape latency and time spent in target quadrants; transfer latency and percentage spontaneous alternations were measured in the MWM, EPM and YM respectively. The animals were anaesthetized with inhalational chloroform and their brains subsequently harvested, homogenized and assayed for acetylcholinesterase24 hours after the experiment. Folate significantly(p